Funkcionalna androgenizacija - Legan, Mateja (Medicinski razgledi, 2001)
Functional hyperandrogenism is common endocrinological disorder of premenopausal women characterized by hyperandrogenism, hirsutism with or without androgenic alopecia and chronic anovulation. The controversy regardingthe pathophysiological mechanism underlying the disease still persists. Insulin resistance and hyperinsulinism are now well recognized features of obese women with functional hyperandrogenism and accepted pathogenetic factor of disorder in obese patients. Insulin enhances lutheotropic hormone secretion and together with it promotes synthesis of androgens in ovaries. Insulin affects the degree of free androgens by loweringserum concentrations of sex-hormone binding globuline. It stimulates synthesis of androgens in adrenal glands and ovaries by enhancing activity of citocrom P450c17alpha. Non-obese women with functional hyperandrogenism have less expressed insulin resistance and higher serum growth hormone concentrations than obese androgenized women as well as weight matched contiols. Higher growth hormone directly and indirectly (through insulin-like growth factor-i) influence ovarian cells end stimulates androgen synthesis: There is possible link between both known aethiopathogenetic factors of functional hyperandrogenism: growth hormone induces insulin resistance and hyperinsulinaemia, which in turn sensitate peripheral tissues for growth hormone.
Keywords: Hiperandrogenizem; Hyperandrogenism; Hiperinzulinemija; Etiology; Hirsutism; Hirzutizem; Insulin resistance; Insulinska rezistenca; Hyperinsulinemia; Estron; Estrone; endokrinologija; Somatotropin; funkcionalna androgenizacija; insulin; rastni hormon